A comparative study of the features in Syriac Arabic and Samaritan Arabic, exploring their similarities and differences as Semitic languages - Hashim Taha Raheem; Nihad Hasan Haji (Zanco Journal of Humanity Sciences)
In the Middle Ages, many literary productions emerged in Arabic language written by the Syriacs and Samaria, known as the science of Semitic languages, mediated with (Syriac Arabic; Samaritan Arabic) texts. These texts share to some extent same linguistic features due to their bilingual nature. They have been written in Arabic Language. In this paper, It is noticed that there are many textual evidences and examples from the Sacred Book that can be identified to prove the shared linguistic features of Semitic languages as well as clarifying the concept of intermediate Semitic languages.